PERBANDINGAN EFEKTIVITAS SENAM AEROBIK DAN SENAM YOGA TERHADAP PENURUNAN TEKANAN DARAH PADA LANSIA DI DESA MEDAN ESTATE - Meini Ceriah Hati Gulo; Lam Murni Sagala (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Background: According to the World Health Organization (WHO), an elderly person is someone who has reached the age of 60 years and above. Among the many diseases that occur among the elderly, hypertension is the cause of death of 17.9 million people in the world every year, where this number covers +31% of all deaths. Hypertension is a cardiovascular disease or blood pressure that increases beyond normal values. Hypertension is an increase in systolic blood pressure of 140 mmHg or 90 mmHg in diastolic blood pressure. Purpose of the study: to analyze the differences in the effectiveness of aerobic exercise and yoga exercise on reducing blood pressure in the elderly in the Medan Estate village. Type of method: the research used in this study is quantitative research, namely experimental research with a Quasy Experimental approach. Using the two-group pre-test and post-test design method. The sampling technique used is total sampling. The number of respondents consisted of 40 people. The exercise was given for 20 minutes per day. Conclusion: The Wilcoxon Signed Ranks Test analysis yielded a Z-value of -2.224 with a significance value (Asymp. Sig. 2-tailed) of 0.025. The significance value of 0.025 is less than 0.05 (p < 0.05), so it can be concluded that there is a significant difference between blood pressure after aerobic exercise intervention and blood pressure after yoga exercise intervention in the elderly in Medan Estate Village.